A signal-on fluorescent biosensor for mercury detection based on a cleavable phosphorothioate RNA fluorescent probe and metal–organic frameworks. Issue 43 (27th October 2022) - Mei, Yang; Yang, Si; Li, Chenxi; Chen, Wenliang; Liu, Rong; Xu, Kexin
Abstract : Schematic diagram of the biosensor for the detection of Hg 2+ based on a cleavable phosphorothioate RNA fluorescent probe quenched by an MOF. Abstract : Mercury contamination is a major environmental concern. In this work, we used a cleavable phosphorothioate (PS) fluorescence probe quenched by UiO-66-NH2 to develop a "signal-on" fluorescent biosensor for Hg 2+ detection. The probe was bound to UiO-66-NH2 through π–π stacking and hydrogen bonding, thereby extinguishing the fluorescence of the FAM-labelled probe. The PS site was cleaved in the presence of Hg 2+, releasing the FAM group and significantly enhancing the fluorescence signal. The intensity of the fluorescence linearly rose as the Hg 2+ concentration increased in the range of 1–100 nM ( R 2 = 0.994), and the limit of detection was 0.118 nM (S/N = 3). This biosensor demonstrated high selectivity for Hg 2+ and was effectively applied to quantification of Hg 2+ in various water samples with acceptable recovery rates. These results suggest that this practical, straightforward technology is a good option for monitoring mercury ions in the environment.